Addition of an affected family member to a previously ascertained autosomal recessive nonsyndromic hearing loss pedigree and systematic phenotype-genotype analysis of splice-site variants in MYO15A - Jin-Yuan Yang; Wei-Qian Wang; Ming-Yu Han; Sha-Sha Huang; Guo-Jian Wang; Yu Su; Jin-Cao Xu; Ying Fu; Dong-Yang Kang; Kun Yang; Xin Zhang; Xing Liu; et al. (BMC, 2022)
Abstract Pathogenic variants in MYO15A are known to cause autosomal recessive nonsyndromic hearing loss (ARNSHL), DFNB3. We have previously reported on one ARNSHL family including two affected siblings and identified MYO15A c.5964+3G > A and c.8375 T > C (p.Val2792Ala) as the possible deafness-causing variants. Eight year follow up identified one new affected individual in this family, who also showed congenital, severe to profound sensorineural hearing loss. By whole exome sequencing, we identified a new splice-site variant c.5531+1G > C (maternal allele), in a compound heterozygote with previously identified missense variant c.8375 T > C (p.Val2792Ala) (paternal allele) in MYO15A as the disease-causing variants. The new affected individual underwent unilateral cochlear implantation at the age of 1 year, and 5 year follow-up showed satisfactory speech and language outcomes. Our results further indicate that MYO15A-associated hearing loss is good candidates for cochlear implantation, which is in accordance with previous report. In light of our findings and review of the literatures, 58 splice-site variants in MYO15A are correlated with a severe deafness phenotype, composed of 46 canonical splice-site variants and 12 non-canonical splice-site variants.